The Wonders of Diptera - Characteristics, Diversity, and Significance for the World's Ecosystems 2021
DOI: 10.5772/intechopen.95924
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Manipulation: A Potential Tool for Mosquito Vector Control

Abstract: Mosquito borne diseases have continued to ravage man and his animals despite efforts to curb its spread. The use of chemicals has been the main thrust for control of all life stages of mosquitoes. Increased resistance to commonly used insecticides has called for renewed effort for vector control. Environmental management for vector control is one of the new strategies developed to tackle the menace of vectors. Manipulation of abiotic factors has widely gained acceptance due to laboratory and semi-field trials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 95 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…Recently, a previous study conducted by our research team revealed a significant positive correlation between larval density and temperature, dissolved oxygen, and salinity in the coastal zone of Benin [11]. Additionally, Ukubuiwe et al [12] found that mosquito larvae can adapt to higher ambient pH levels than other aquatic organisms. In Western Kenya, a study showed a positive correlation between anopheline abundance and nitrate levels in water, while negative but significant correlations were observed with iron levels in water and biofilm cover on the water surface [13].…”
Section: Introductionmentioning
confidence: 73%
“…Recently, a previous study conducted by our research team revealed a significant positive correlation between larval density and temperature, dissolved oxygen, and salinity in the coastal zone of Benin [11]. Additionally, Ukubuiwe et al [12] found that mosquito larvae can adapt to higher ambient pH levels than other aquatic organisms. In Western Kenya, a study showed a positive correlation between anopheline abundance and nitrate levels in water, while negative but significant correlations were observed with iron levels in water and biofilm cover on the water surface [13].…”
Section: Introductionmentioning
confidence: 73%
“…Recently, a previous study conducted by our research team revealed a signi cant positive correlation between larval density and temperature, dissolved oxygen, and salinity in the coastal zone of Benin [11]. Additionally, Ukubuiwe et al [12] found that mosquito larvae can adapt to higher ambient pH levels than other aquatic organisms. In Western Kenya, a study showed a positive correlation between anopheline abundance and nitrate levels in water, while negative but signi cant correlations were observed with iron levels in water and bio lm cover on the water surface [13].…”
Section: Introductionmentioning
confidence: 75%
“…Both processes enable insects to either avoid or shorten interaction with the hazardous compound. Comparing behavioural resistance to biochemical insensitivity and resistance by changing the appropriateness accuracy of insecticides, it is more challenging to monitor field populations and use relatively simple exposure assays, which contributes to the scarcity of data on behavioural resistance [15] .…”
Section: Variation In Their Ecology Changes In the Behavior And Avoid...mentioning
confidence: 99%